Adapting a community first aid responder programme to increase out-of-hospital capacity in Kinshasa, Democratic Republic of Congo - Diango, Ken Ngoy (Division of Emergency Medicine, 2025)
In 2023, the seventy-sixth World Health Assembly passed a significant resolution – WHA76.2 – calling for global efforts to strengthen the provision of quality Emergency, Critical, and Operative care (ECO) to address the growing burden of acute and critical illnesses, particularly in low- and middle-income countries (LMICs). In areas where formalised prehospital care systems are being established to improve outcomes, the incorporation of a layperson first responder programme could facilitate greater access to care for individuals in need and serve as an effective initial intervention to bolster out-of-hospital emergency care (OHEC) capacity. WHO developed the Community First Aid Response (CFAR) training program to support this approach. For the course to be appropriately and sustainably implemented, contextual adaptations are necessary. The prerequisites for this country-specific adaptation include, among other factors, a systematic evaluation of the country's emergency care landscape, a needs assessment and understanding the acceptability of the proposed intervention. Aim and Objectives: The aim of the thesis was to adapt a country-specific CFAR program for the Democratic Republic of Congo (DRC) as an initial intervention to increase OHEC capacity. Four studies were planned to fulfil the main objectives. The first was to outline the key functions and related components of the country's emergency care system, identify the gaps, and define priority areas for strengthening. The second was to evaluate community needs for, and the availability of, emergency care services in Kinshasa, DRC, to determine the nature and magnitude of unmet needs, especially in OHEC. The third study was to assess the usefulness and acceptability of an adapted CFAR programme designed to strengthen OHEC capacity in Kinshasa. The fourth and final study was to describe and assess a pilot CFAR course, including the process, resources, curriculum, and teaching methods, while also capturing knowledge and confidence gains from the perspectives of both organisers and participants. Methods: A series of four studies was carried out in Kinshasa, DRC. The first study used a consensus method to describe essential components of the country's emergency care system utilizing the WHO Emergency Care System Assessment (ECSA) tool. The second study involved a household survey that contrasted the needs and availability of emergency care services within Kinshasa's communities. The third utilized focus groups to evaluate the usefulness and acceptability of an adapted CFAR programme. The final study consisted of a feasibility assessment using mixed methods analysis to describe and assess core elements of the implementation of a pilot CFAR training and provide key outcomes. Results: The evaluation of the DRC ECSA revealed several gaps, including an inadequate OHEC capacity. The household survey indicated significant unmet needs in the provision of emergency care, particularly regarding out-of-hospital services. An adapted CFAR program was recognised as a suitable and acceptable strategy to increased OHEC capacity in Kinshasa. Finally, a CFAR pilot was successfully conducted and found to be contextually relevant, representing a potential initial step to address the existing OHEC capacity shortfalls in Kinshasa. Conclusion: This dissertation offers significant conceptual, analytical, and empirical insights into the context-specific adaptation of a CFAR program as an initial intervention to increase OHEC capacity in a nascent emergency care system of a resource-constrained setting. Our results suggest that a comprehensively implemented tailored system could potentially enhance OHEC capacity in low-resource settings and likely impact outcomes.